Prediction of axial load capacity of concrete walls with openings restrained on three sides. (October 2020) - Ho, Nhat-Minh; Doh, Jeung-Hwan; Fragomeni, Sam; Yang, Jiacheng; Yan, Kai; Guerrieri, Maurice
Abstract: Currently, the empirical wall design equations given in major codes of practices either offer no guidelines or provide overly conservative predictions of the ultimate axial strength of concrete walls with openings restrained on three sides (TW3S walls with openings). In view of the significant shortcomings, an appropriate design equation is required for such walls. This paper presents a numerical investigation on the behaviour of TW3S walls with openings under eccentric axial loading. A finite element model using the ABAQUS software was employed to undertake parametric studies examining the influence of opening parameters, which consisted of configuration and location, on the axial load capacity of TW3S walls. In total, 101 models were developed and analysed. Having established the relationships between the opening parameters and the ultimate load capacity of TW3S walls, a more encompassing design equation was derived. The reliability of the proposed equation was ascertained through comparisons with available test data.